2018
DOI: 10.1521/pedi_2017_31_303
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Traits of Schizotypy Associated With Glycine Receptor GLRA1 Polymorphism: An Exploratory Candidate-Gene Association Study

Abstract: Schizotypy captures the underlying genetic vulnerability to schizophrenia. However, the genetic underpinnings of schizotypy remain unexplored. The authors examined the relationship between single nucleotide poly-morphisms (SNPs) and schizotypy. A sample of 137 subjects (43 healthy controls, 34 subjects with schizotypal personality disorder [SPD], 32 with borderline personality disorder, and 25 with other personality disorders) completed the Schizotypal Personality Questionnaire (SPQ). Subjects were genotyped u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…By finding the closest DE expressed protein coding genes to DE ncRNAs between HFP and LFP chickens we were able to identify 21 putative eRNAs (Table 1). Among possible targets of these eRNA candidates are ARHGEF38 and SH3YL1, which have been linked to bipolar disorder and suicide [47,48], GLRA1 and MCTP2 were found to be associated with schizophrenia [49,50], and CHIR-B3, MHCIA7, MHCIY as well as MICA are genes involved in the immune system [51]. Thus, further experiments, like overexpression studies, will help to clarify the involvement of particular ncRNAs in FP.…”
Section: Discussionmentioning
confidence: 99%
“…By finding the closest DE expressed protein coding genes to DE ncRNAs between HFP and LFP chickens we were able to identify 21 putative eRNAs (Table 1). Among possible targets of these eRNA candidates are ARHGEF38 and SH3YL1, which have been linked to bipolar disorder and suicide [47,48], GLRA1 and MCTP2 were found to be associated with schizophrenia [49,50], and CHIR-B3, MHCIA7, MHCIY as well as MICA are genes involved in the immune system [51]. Thus, further experiments, like overexpression studies, will help to clarify the involvement of particular ncRNAs in FP.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-Resistant Schizophrenia and Glycine Signaling subunit (GLRA1) gene, and dimensional schizotypy, specifically with the disorganized symptoms cluster (199). Further support for a role of the glycinergic system comes from a genetic-metabolomic study (200), which showed that 5-oxoproline, aspartate, and glutamate, known to affect NMDAR function, were significantly elevated in patients with rare variants in genes encoding for the glycine cleavage system.…”
Section: Genetics Of Glycinergic Pathway In Schizophreniamentioning
confidence: 99%